Pengaruh pelatihan, pengembangan kapasitas dan pemberian reward terhadap peningkatan kinerja sumber daya manusia - Susi Ramayanti (Jurnal Kajian Manajemen dan Wirausaha, 2022)
The tourism potential in Kapalo Banda Taram has not been fully balanced with the institutional capabilities and members of the tourism awareness groups, especially in managing the Kapalo Banda. It is become interesting to examine the performance of the tourism manager. This study aimed to analyze how performance is influenced by the variables of training, capacity building and reward. The results of this study partially show that there is a significant effect of training on performance, there is an insignificant effect of capacity development on performance, there is a significant effect of giving rewards on performance.